Critical Contribution of NK Group 2 Member D Expressed on Invariant Natural Killer T Cells in Concanavalin A-Induced Liver Hepatitis in Mice - Al Dulaimi, Dina; Klibi, Jihene; Olivo Pimentel, Veronica; Parietti, Veronique; Allez, Matthieu; Toubert, Antoine; Benlagha, Kamel (Frontiers in Immunology, 2018)
Natural killer group 2D (NKG2D) is a well-characterized activating receptor expressed on many immune cells, including invariant natural killer T (iNKT) cells. These cells were shown to be responsible of liver injury in the model of concanavalin A (Con A)-induced hepatitis, considered to be an experimental model of human autoimmune hepatitis. In this study, we investigated whether NKG2D plays a role in the hepatitis induced by iNKT cell-mediated immune response to Con A. By using killer cell lectin-like receptor subfamily K, member 1 deficient (Klrk1−/−) mice, we found that the absence of NKG2D reduced the hepatic injury upon Con A administration. This was not due to an intrinsic functional defect of NKG2D-deficient iNKT cells as mice missing NKG2D have normal distribution and function of iNKT cells. Furthermore, increased resistance to Con A-induced hepatitis was confirmed using neutralizing anti-NKG2D antibodies. The reduced pathogenic effect of Con A in the absence of NKG2D correlates with a reduction in pathogenic cytokine production and FAS-Ligand (FAS-L) expression by iNKT cells. We also found that Con A administration led to an increase in the retinoic acid early inducible (RAE-1) surface expression on wild-type hepatocytes. Finally, we found that Con A has no direct action on FAS-L expression or cytokine production by iNKT cells and thus propose that NKG2D-L expression on stressed hepatocytes promote cytotoxic activity of iNKT cells via its interaction with NKG2D contributing to hepatic injury. In conclusion, our results highlight NKG2D as an essential receptor required for the activation of iNKT cells in Con A-induced hepatitis and indicate that it represents a potential drug target for prevention of autoimmune hepatitis.